Rotavirus epidemiology before and after vaccine introduction - Andrêssa S.F. Assis; Daniel A. Valle; Gustavo R. Antunes; Sandra H.C. Tibiriça; Rosane Maria S. de Assis; José Paulo G. Leite; Iná P. de Carvalho; Maria Luzia da Rosa e Silva (Brazilian Society of Pediatrics, 2013)
Objectives: To evaluate the prevalence and circulation of rotavirus genotypes before and after the introduction of oral vaccine against human rotavirus (OVHR), and to check for a possible change in the age of occurence of the infection by RV-A. Methods: This was a cross-sectional study conducted between 2002-2011, in the city of Juiz de Fora, state of Minas Gerais, Brazil. A total of 1,144 diarrheal stool specimens were obtained from nonhospitalized children aged between 0 and 5 years, and analyzed by polyacrylamide gel electrophoresis and reverse-transcription polymerase chain reaction for genotype characterization. Data on prevalence and age distribution of rotavirus cases were analyzed through the chi-squared test (p < 0.05), using SPSS, release 13.0. Results: Rotavirus infection was detected in 9.35% (107/1,144) samples, with prevalence rates ranging from 11.12% (90/809) in the pre-vaccine to 5.07% (17/335) in the post- vaccine period (p = 0.001). Among the samples tested, the most frequently detected genotypes were G1P[6] (6/33 = 18.2%) in the period between 2002 and 2005 and G2P[4] in 2006 (11/33 = 33.3%) and in the period between 2007 and 2011 (5/33 = 15.2%). There was also a significant reduction in the number of cases of rotavirus disease in children aged between 0 and 36 months after the vaccine introduction. Conclusions: The study evidenced a significant decrease in the prevalence of rotavirus, mainly in children aged between 0 and 36 months in the 2007-2011 period, as well as a reduction in G1 genotype circulation.